2023
DOI: 10.3389/fcvm.2023.1093255
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationship between atrial fibrillation and leukocyte telomere length: A two sample, bidirectional Mendelian randomization study

Abstract: BackgroundAtrial fibrillation (AF) is an age-related disease, while telomeres play a central role in aging. But the relationship between AF and telomere length (LTL) is still controversial. This study aims to examine the potential causal association between AF and LTL by using Mendelian randomization (MR).MethodsBidirectional two-sample MR, expression and protein quantitative trait loci (eQTL and pQTL)-based MR were performed using genetic variants from United Kingdom Biobank, FinnGen, and a meta-analysis stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that H3C4 is involved in the epigenetic regulation of gene expression [ 38 ], nucleosome assembly [ 39 ], and telomere organization [ 40 ]. Previous studies found that telomeres can maintain chromosomal stability and are associated with ageing and longevity [ 41 , 42 ]. Although tRF-Trp-CCA-014 did not affect cell senescence, it may regulate the expression level of H3C4 mRNA and protein to function in ageing; otherwise, the H3C4 isoforms of human, mouse, and fruit fly are conserved.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that H3C4 is involved in the epigenetic regulation of gene expression [ 38 ], nucleosome assembly [ 39 ], and telomere organization [ 40 ]. Previous studies found that telomeres can maintain chromosomal stability and are associated with ageing and longevity [ 41 , 42 ]. Although tRF-Trp-CCA-014 did not affect cell senescence, it may regulate the expression level of H3C4 mRNA and protein to function in ageing; otherwise, the H3C4 isoforms of human, mouse, and fruit fly are conserved.…”
Section: Discussionmentioning
confidence: 99%
“…The IVW approach was applied as the main MR model, which provides most accurate estimate under the assumption that the instrumental variables were all valid ( 39 ). In order to account for potential heterogeneity and horizontal pleiotropy, three additional approaches for MR analyses including MR-Egger regression, weighted median and weighted mode methods, were applied.…”
Section: Methodsmentioning
confidence: 99%
“…This may suggest that accelerated telomere shortening is secondary to the onset of AF. This year, a Mendelian analysis was presented, indicating such a cause-and-effect relationship [117]. The consequences of AF incidence, however, make this novel inverse relationship difficult to explain.…”
Section: Telomeres and Afmentioning
confidence: 99%